Factors that predict the perception of spirituality and spiritual care of nurses working in high-risk units and the effect of death anxiety - Rahman, Suheyla; Elbi, Huseyin; Cakmakci Cetinkaya, Aynur; Altan, Selim; Ozan, Erol; Pirincci, Edibe (Wiley, 2021)
Purpose Spirituality contributes to the health and well-being of individuals. This study investigates the factors that predict the spirituality perceptions and the effect of death anxiety of nurses. Design and Methods This was a cross-sectional study, 382 nurses working in four public hospitals intensive care and emergency departments setting in two different cities in Turkey. Findings Variables predicting the total and subscale scores of the Spirituality and Spiritual Care Rating Scale of nurses were determined by linear multiple regression analysis. Except for the religiousness subscale, the satisfaction level of nurses was found to be a significant predictor in total of Spirituality and Spiritual Care Scale. Practice Implications Nurses working in high-risk units are unclear about their perception of spirituality and spiritual care.
Keywords: death anxiety; nurse; spiritual care; spirituality